LONG-TERM RESULTS OF RECONSTRUCTION OF THE INFERIOR MESENTERIC AND INTERNAL ILIAC ARTERIES DURING RESECTION OF THE ANEURYSM OF THE INFRARENAL AORTIC SEGMENT - A. Ya. Bedrov; A. A. Moiseev; A. V. Belozertseva; A. N. Morozov; Yu. A. Pugachenko (Вестник хирургии имени И.И. Грекова)
The  OBJECTIVE   is  to  assess the  patency  of  the  inferior  mesenteric artery   and   internal   iliac  arteries in  the  remote period  after  resection of the  aneurysm of the  infrarenal  aortic  segment. MATERIAL AND METHODS.  The  study  included 33  patients who  underwent resection  of  the  abdominal aortic  aneurysm with  reconstruction of  the  inferior  mesenteric artery  and  (or)  internal  iliac  arteries from  1998  to  2017.   All patients were  examined with  computed  tomography scan with  contrast to  assess the  patency of  inferior  mesenteric artery  and   internal  iliac  arteries. RESULTS.   Patients  were observed from  0.5  to  15  years. Among  30  patients with  inferior  mesenteric artery   implanted  into  the  prosthesis,  23 (76  %)  patients had  a  passable inferior  mesenteric artery  and  7  patients had  an  occluded inferior  mesenteric artery. The  implanted  inferior  mesenteric artery   maintained its  patency for  3  years in  100%   of  cases, from  3  to  5  years  – in  86%,  after  5  years and   more   –  in  62%.  In  one   patient   who  underwent  reconstruction  of  the  internal   iliac  artery, thrombosis  of  the  prosthetic-internal  iliac  shunt   was   found  out  in  1.5  years  after  the  operation,  without  any  clinical manifestations. One  patient,  underwent the  reconstruction of the  internal  iliac artery,  was  diagnosed with thrombosis of the prosthetic-internal iliac  shunt   in  1.5  years after  the  operation, which  was   not  accompanied by  clinical  manifestations. CONCLUSION.  The  high  remote patency of the  inferior mesenteric artery  and  internal  iliac arteries reconstructed during resection of the aneurysm of the infrarenal aortic segment indicates the need for this procedure in order to prevent ischemic disorders of the digestive organs and pelvis.